(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the effect of cause of death on postmortem Sodium, Potassium and Chloride levels in cerebrospinal fluid. Study Design: Observational study Place and Duration of Study: This study was conducted at the Forensic Medicine Department, King Edward Medical University (KEMU), Lahore for a period of 6 months from December 2013 to June 2014. Materials and Methods: Medicolegal autopsy cases were included in which the exact cause and time of death were known. A total number of consecutive 106 samples were collected. Unknown and putrefied dead bodies, Poisoning cases and Cases with head injuries were not included. Study was completed in 6 months. Results: The K+, Na+and Cl- levels are significantly affected by certain causes of death. Conclusion: Biochemistry of Cerebrospinal Fluid alone may not be very useful in postmortem interval estimation.